Answer :

Answer:

(-2,-6)

Step-by-step explanation:

Answer:

Step-by-step explanation:

Substitute 5x+4 for y in the second equation.

5x+4 = -3x-12

add 3x to both sides to have x on one side

8x + 4 = -12

substract 4 on both sides to isolate the x.

8x=-16

x=-2

solve for y by putting the value of x in either equation.

y=5(-2) + 4

y=-6

or

y=-3(-2)-12

y=6-12

y=-6

ANSWER (-2,-6)

check answer by putting x and y values in either equation to make sure they equal

Y=5x + 4

-6=5(-2)+4

-6=-10+4

-6=-6

Other Questions